Performance of Cunninghamia lanceolata / Uncaria Composite Particleboard - Qiaoyan Zhang; Longxu Wu; Huagang Liao; Qingqing Yang; Haiyuan Yang; Yang Yang; Xin He; Linjing Lan; De Li; Zhigang Wu (BioResources)
Particleboards were prepared with thinning wood of Cunninghamia lanceolata (Chinese fir) and wood shavings of waste Uncaria sinensis branches by using melamine-urea-formaldehyde resin as the adhesive. Influences of particle mass ratio of C. lanceolata to Uncaria, adhesive loading, and target density on internal bonding strength (IB), modulus of rupture (MOR), modulus of elasticity (MOE), thickness swelling rate of water absorption (TS), and water absorption (WA) of the composite particleboard were investigated. Results showed that: (1) IB, MOR, MOE, 2h-TS, and 2h-WA of pure C. lanceolata particleboard met service requirements of type-P2 furniture particleboard of GB/T 4897-2015. (2) With the increase of Uncaria particles, IB of composite particleboard decreased gradually, while MOR, MOE, TS, and WA first increased and then decreased. The best comprehensive performances were achieved when the mass ratio of C. lanceolata to Uncaria was 75:25, manifested by 1.5 MPa of IB, 21.3 MPa of MOR, 2140 MPa of MOE, 2.4% of 2h-TS and 12.3% of 2h-WA. These performances basically meet the service requirements on type-P3 of the standard. (3) It can make C. lanceolata fir/Uncaria particleboard meet requirements on type-P4 heavy-load particleboard of the standard by increasing target density and adhesive loading appropriately. (4) The C. lanceolata/Uncaria composite particleboard showed higher thermostability and fire resistance.